2021
DOI: 10.31235/osf.io/x3qr6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Use of Ai (Artificial Intelligence) in English Learning Among University Student: Case Study in English Department, Universitas Airlangga

Abstract: Aim: This research aim is to analyze an artificial intelligence platform that can be used in imparting education as well as evaluating student performance. Method: This research was conducted with a qualitative method by conducting in-depth interviews and a literature study. Results: The findings of this study shows that Artificial Intelligence technology can be used as a means of developing English learning for students. Discussion: There have been several studies that support research results, that AI can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…APPENDIX Table 3. Success factors (critical success factor) ( [1], [3], [4], [6]- [10], [27]- [36], [37]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…APPENDIX Table 3. Success factors (critical success factor) ( [1], [3], [4], [6]- [10], [27]- [36], [37]…”
Section: Discussionmentioning
confidence: 99%
“…The report encompassed policy concepts and design suggestions based on decision making revision of development of AI learning model as shown in Table 1 2 shows the characteristics of Purbalingga 1 Public Vocational School and Telkom Vocational High School according to the expertise competences. Success factor (critical success factor) [1], [3], [4], [6]- [10], [27]- [36], [37]- [43], of 55 respondents, in teaching factory learning based on AI, based on the potential of students at SMK Negeri 1 Purbalingga and Telkom SMKS in Central Java Province as shown as Table 3 (see in Appendix). The findings from the calculations presented in Table 3 demonstrate the content validity coefficient for each of the five success factor items.…”
Section: Reporting the Findings Of Research Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research, this application improved students' grammar understanding by providing personalized training based on student performance data and providing rapid feedback on their replies. Similarly, Dewi et al (2021) investigated prominent AI-based services such as Duolingo, Google Translate, and Grammarly to confirm the usefulness of AI in educational contexts. The study's findings indicated that AI has a good influence on English language learning and that it should be included in English language instruction to enhance student learning outcomes.…”
Section: Ai and The Use Of Ai In Language Learning And Teachingmentioning
confidence: 99%
“…Having the same mindset, Park (2019) affirmed that implementing AI in the form of a grammar checker could assist in lowering students' grammatical errors in their written works. Dewi et al (2021) strengthened the notion by reiterating AI's benefits for improving students' language skills. Clearly, incorporating AI into language learning and teaching results in enhanced learning outcomes for students, as it provides them with ample opportunities for The researcher's practical experience in teaching various writing courses at the Faculty of Foreign Languages, Van Lang University, has highlighted the significant challenge of limited individual interaction between teachers and students in crowded classes.…”
Section: Introductionmentioning
confidence: 99%